A glance on legal system bioethics matters’ status on infertility in Peru - Siverino Bavio, Paula (2014)
The article explores from the bioethics’ interdisciplinary perspective some of the most compelling questions on the legal framework of assisted reproduction techniques in Peru. Methods used are based on dogmatic-exegetical analysis.